Integrated optimisation of stope boundary and access layout for underground mining operations. Issue 4 (2nd October 2019) - Hou, Jie; Xu, Chaoshui; Dowd, Peter Alan; Li, Guoqing
ABSTRACT: For underground mines, two major designs that need to be optimised are the stope boundary and the access layout. The optimisation of these two components cannot be done independently as ore extracted from stopes is transported to the surface via the access network. Different stope locations result in different associated access development costs. This paper describes a proposed integrated optimisation model to optimise stope and access layouts simultaneously. The interactions and interdependency between stopes and access are ensured by a dynamic access development cost analysis based on recursive computations. Mixed integer non-linear programming is used to maximise the overall economic value subject to the constraints of generating optimal stopes and access layout, which is solved by a Genetic Algorithm modified for computational efficiency. A stratiform gold deposit is used as a case study to demonstrate that the new approach can provide a more profitable solution compared with traditional approaches.